Editorial: Local Islam and Current Issues (Al-Jamiah Research Centre, 2013)
Themes in this edition vary ranging from feminism, literature, films, politics, charitable organization, Sufism, to the relation of Islam and Soviet Union, and the relation of a Jewish group and Islam. To begin with, the paper by Laila Khalid Alfirdaus presents the analysis of the involvement of kyais (religious teachers) in local political affairs in Kebumen Central Java during the reform period. Due to their charisma in Indonesian society, kyais had advantage in entering politics in the period. However, Alfirdaus sees that their involvement in politics does not always lead to the birth of better impact on public policy. In the case of Kebumen, the leadership of a kyai in the governmental body was marked by lessening development in terms of public infrastructure and social services.